Imported malaria in the UK, 2005 to 2016: Estimates from primary care electronic health records - Bastaki, Hamad (PLoS One, 2018)
OBJECTIVE: To investigate trends in the incidence of imported malaria in the UK between 2005 and 2016. DESIGN: Analysis of longitudinal electronic health records (EHRs) in The Health Improvement Network (THIN) primary care database. SETTING: UK primary care PARTICIPANTS: In total, we examined 12,349,003 individuals aged 0 to 99 years. OUTCOME MEASURE: The rate of malaria recordings in THIN was calculated per year between 2005 and 2016. Rate ratios exploring differences by age, sex, location of general practice, socioeconomic status and ethnicity were estimated using multivariable Poisson regression. RESULTS: A total of 1,474 individuals with a first diagnosis of malaria were identified in THIN between 2005 and 2016. The incidence of recorded malaria followed a decreasing trend dropping from a rate of 3.33 in 2005 to 1.36 cases per 100,000 person years at risk in 2016. Multivariable Poisson regression showed that adults of working age (20 to 69 years), men, those registered with a general practice in London, higher social deprivation and non-white ethnicity were associated with higher rates of malaria recordings. CONCLUSION: There has been a decrease in the number of malaria recordings in UK primary care over the past decade. This decrease exceeds the rate of decline reported in national surveillance data; however there are similar associations with age, sex and deprivation. Improved geographic information on the distribution of cases and the potential for automation of case identification suggests that EHRs could provide a complementary role for investigating malaria trends over time.